2011
DOI: 10.1590/s1516-35982011001100034
|View full text |Cite
|
Sign up to set email alerts
|

Levels of ground corn supplied to beef heifers at pasture during the rainy season: productive performance, intake, digestibility and microbial efficiency

Abstract: -The objective was to evaluate the effect of four levels of ground corn supply on nutritional parameters, microbial synthesis efficiency and growing performance of beef heifers, at the rainy season. For such, 28 crossbred yearling heifers, with initial age of 16-17 months and initial weight of 255 ± 31.0 kg were distributed into five paddoks of B. decumbens, of 2.0 ha each, with average potentially digestible DM availability of 2,377.0 kg/ha. For each one of the lots, one of the following supplements was daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Even though supplementation provided increases in DM digestibility during the rainy season, all nutritional plans had similar intakes of DM and TDN. Although some authors ( Nascimento et al, 2010 ; Figueiredo et al, 2011 ) observed increases in TDN intake without changes in DM intake due to the many factors that make treatment effects less visible over cattle on pasture condition, other authors ( Figueiredo et al, 2008 ; Barros et al, 2011 ) did find differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though supplementation provided increases in DM digestibility during the rainy season, all nutritional plans had similar intakes of DM and TDN. Although some authors ( Nascimento et al, 2010 ; Figueiredo et al, 2011 ) observed increases in TDN intake without changes in DM intake due to the many factors that make treatment effects less visible over cattle on pasture condition, other authors ( Figueiredo et al, 2008 ; Barros et al, 2011 ) did find differences.…”
Section: Discussionmentioning
confidence: 99%
“…Energetic supplements usually increase the amount of total energy intake, mainly by directly supplying energy from supplements, since normally there is no increase in pasture intake ( Figueiredo et al, 2011 ). Thus, the energetic supplement (LPHC, 15% CP) provided lower fiber digestibility with similar TDN intake when compared to the other supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Una de las herramientas nutricionales para optimizar el comportamiento productivo y reproductivo de novillas pastoreando, es la suplementación energética (Lobato, 2009) y el uso de aditivos como el antibiótico virginiamicina, que ha mostrado tener una eficiencia en el control de acidosis en bovinos alimentados intensivamente en corral, con raciones con grano por arriba de la mitad de ración, por lo tanto su utilización, puede promover un mayor rendimiento de ganado criado en pastos (Ferreira et al, 2011). En cuanto a los primeros, cabe destacar la importancia de la sustitución, ya que en general, la suplementación se basa en reemplazar parte de la energía aportada por los pastos disminuyendo el consumo de forraje por animal, a medida que se aumenta el porcentaje de participación del concentrado en la dieta (Figueiredo et al, 2011). El grano de maíz ha sido la materia prima usada por excelencia en Brasil para la fabricación de concentrados energéticos para la producción animal, y su uso se ha visto afectado debido a su diversificación en otros campos como al consumo humano, y uso para fabricación de biocombustibles.…”
Section: Corporaciones Gubernamentales Entes Privados Y El Grupo De Investigación Enunclassified